PENERAPAN MODEL PROBLEM BASED LEARNING BERBENTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR TEMA 8 MUATAN IPA SISWA KELAS V - Ardian Pahlevi; Veryliana Purnamasari; Darsimah Darsimah (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract : Application Of Problem Based Learning Model With Audio Visual Media For Improving Learning Outcomes Theme 8 IPA Content For Class V Students. The background that drives this research is the low learning outcomes of fifth graders at SDN 05 Pedagung. The value of the learning outcomes of the theme 8 Environment of Our Friends for Class V science content where there are still many students who do not meet the KKM, that of 11 students only 4 students (36.36%) have completed and 7 students (63.64%) have not. This is because in learning students cannot think critically in solving problems and solving problems such as what is given by the teacher so that student learning outcomes are less than optimal. Then students are also less active during learning. This study aims to determine the application of the Problem Based Learning (PBL) Learning Model Assisted by Audio Visual Media to Improve Learning Outcomes of Theme 8 Our Friends Environment Contents of Science in Class V Students at SDN 05 Pedagung Pemalang Regency Academic Year 2020/2021. The results showed that the cognitive domain learning outcomes in the first cycle of the first meeting of 11 students 6 students completed and 5 students did not complete with an average calsical percentage of 69.09%, in the first cycle of the second meeting the students who completed increased from 11 students 7 students completed and 4 students did not complete with an average percentage of 71.81%, in the second cycle of the first meeting the students who completed also increased from the previous learning, namely from 11 students 8 completed and 3 students who did not complete with an average percentage the classical average of 74.54%, %, in the second cycle of the second meeting the students who completed did not increase from the previous learning, namely from 11 students,8 students completed and 3 students did not complete, but the classical average percentage increased by 77.27%, % , in the third cycle of the first meeting the students who completed the lesson increased from the previous learning, namely from 11 students 9 students completed and 2 students did not complete with a classical average percentage 78.18%, and %, in the third cycle of the second meeting the students who completed did not increase from the previous learning, namely from 11 students 9 students completed and 2 students did not complete but the classical average percentage increased 80.90%.Keywords : Problem Based Learning model, Audio Visual media, learning outcomes for the themes of 8 of our friends in the science subject Abstrak: Penerepan Model Problem Based Learning Berbantuan Media Audio Visual Untuk Meningkatkan Hasil Belajar Tema 8 Muatan IPA Siswa Kelas V. Latar belakang yang mendorong penelitian ini adalah rendahnya hasil belajar siswa kelas V SDN 05 Pedagung. Nilai hasil belajar tema 8 Lingkungan Sahabat Kita muatan IPA Kelas V yang masih banyak siswa tidak memenuhi KKM yaitu dari 11 siswa hanya 4 siswa (36,36%) yang tuntas dan 7 siswa (63,64%) yang tidak tuntas. Hal ini disebabkan dalam pembelajaran siswa tidak bisa berpikir kritis dalam memcahkan permasalahan dan memcahkan suatu masalah seperti doal yang diberikan oleh guru sehinggal hasil belajar siswa kurang maksimal. Kemudian siswa juga kurang aktif pada saat pembelajaran. Penelitian ini bertujuan untuk mengetahui Penerapan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Audio Visual Untuk Meningkatan Hasil Belajar Tema 8 Lingkungan Sahabat kita Muatan IPA Pada Siswa Kelas V di SDN 05 Pedagung Kabupaten Pemalang Tahun Ajaran 2020/2021. Hasil penelitian menunjukan bahwa hasil belajar ranah kognitif pada siklus I pertemuan I dari 11 siswa 6 siswa tuntas dan 5 siswa tidak tuntas dengan presentase rata-rata kalsikal sebesar 69,09%, pada siklus I pertemuan II siswa yang tuntas meningkat yaitu dari 11 siswa 7 siswa tuntas dan 4 siswa yang tidak tuntas tuntas dengan presentase rata-rata kalsikal sebesar 71,81%, pada siklus II pertemuan I siswa yang tuntas juga meningkat dari pembelajaran sebelumnya yaitu dari 11 siswa 8 siswa tuntas dan 3 siswa yang  tidak tuntas tuntas dengan presentase rata-rata klasikal sebesar 74,54%, %, pada siklus II pertemuan II siswa yang tuntas tidak meningkat dari pembelajaran sebelumnya yaitu dari 11 siswa 8 siswa tuntas dan 3 siswa yang tidak tuntas tuntas tetapi presentase rata-rata klasikal meningkat sebesar 77,27%, %, pada siklus III pertemuan I siswa yang tuntas meningkat dari pembelajaran sebelumnya yaitu dari 11 siswa 9 siswa tuntas dan 2 siswa yang tidak tuntas tuntas dengan presentase rata-rata klasikal sebesar 78,18%, dan %, pada siklus III pertemuan II siswa yang tuntas tidak meningkat dari pembelajaran sebelumnya yaitu dari 11 siswa 9 siswa tuntas dan 2 siswa  yang tidak tuntas tetapi presentase rata-rata klasikal meningkat sebesar 80,90%. Kata Kunci : Model Problem Based Learning, media Audio Visual, hasil belajar tema 8 lingkungan sahabat kita mapel IPA.